Implementation of Divorce in Bali Society Related to National Marriage Law - Sukerti, Ni Nyoman; Ari Krisnawati, I G.A.A. (Udayana Journal of Social Sciences and Humanities; Vol 2 No 2 (2018): UJoSSH, September 2018DO - 10.24843/UJoSSH.2018.v02.i02.p03, 2018)
This study aims to explore and analyze the implementation of divorce in the Village Pakraman Kubu, Kubu Village, Bangli. This research is socio-legal research, which relies on field data as primary data. Data were extracted by interview, then processed and analyzed qualitatively. The results show that in the last ten years there have been six divorced couples and none of this has been done before the court. Divorce is done customarily for various reasons, because it is very simple, does not understand the Marriage Law, through the court hearing takes a long time and cost more. This is due to the attitude, behavior or legal culture of the people who prefer to deviate from the national marriage law and the lack of socialization from related parties. Thus the Marriage Law has not been influential in the implementation of the divorce. The conclusion is that the divorce remains customary so the marriage law has not reflected any influence on the implementation of the divorce.